Dominant Language Learning Strategies Used by Managemen Dakwah Department Students at UIN MATARAM - Afif Ikhwanul Muslimin (EDULANGUE, 2019)
AbstractOne of the prominent skills to be acquired by English language learners is Language learning strategies (LLSs) which is significant to enhance communicative competence. Individual’s differences in using the strategies depict their understanding on LLSs. An interesting fact on the result of Manajemen Dakwah Department Students (MDDSs) at State Islamic University (UIN) of Mataram in the odd semester of academic year 2018-2019 was 64 students got higher average English scores in their final test (88) compared to their middle test (65) that might reflect different use of LLS. The English subject was focusing on reading comprehension. Furthermore, descriptive qualitative case study was applied to record the dominant LLSs used by ten successful students or achievers in English class who has the criteria of achieving English score above 90. Three instruments were used to gather data, they are: documentation, questionnaire, and interview. The result shows that students used all LLSs and creating their own learning opportunities. Only HN that did not use social strategy though he used all other strategies. It means that successful MDDSs believe that exactly all LLSs are significant for elevating their language learning. Another result shows that the dominant LLSs which were used are compensation as they are good guesser for the unfamiliar words, memory strategy since they always try to memorize to retain the vocabulary in mind, and metacognitive strategy where they always create best setting for them to learn. Keywords: Language Learning Strategies, MDDSs, Dominant LLSs, English Scores.